Pengembangan E-Modul Pembelajaran Berbasis Virtual Laboratory Platform Tinkercad untuk Pembelajaran Teknik Listrik dan Elektronika - Arista Riski Munandar; Muhammad Kholil (Nozel : Jurnal Pendididikan Teknik Mesin, 2026)
This research aims to produce a learning e-module for Basic Electronic Engineering Virtual Laboratory Tinkercad in the Electrical and Electronic Engineering course of the Mechanical Engineering education study program, FKIP UNS, to determine the level of feasibility and practicality of the resulting e-module. This research is a type of research and development (R&D). The module development procedure adapts the Four-D model limited to only 3 stages, namely, 1) Define, 2) Design, 3) Develop. The research involves material experts, media experts, and language experts to assess the feasibility of the module. Students were also involved to obtain feedback on the module's practicality. Data collection used a questionnaire analyzed using descriptive statistics. The research resulted in a Tinkercad Virtual Laboratory Basic Electronics Engineering e-module containing the title, topic, learning objectives, subject matter, circuit simulation activities, practice questions and answer keys, and bibliography. The e-module's feasibility rating, based on assessments by learning media experts, was 94.4%, material experts 87.2%, and language experts 84.2%, categorizing it as highly feasible. Furthermore, the practicality rating, based on the trial scores obtained by 77 PTM students from the Class of 2026, was 81%, categorizing it as practical.